TYPE 2 DIABETES MELLITUS PATIENTS’ COMPREHENSION OF HYPOGLYCEMIA: A LONG AND WINDING ROAD TO OPTIMAL CARE OF DIABETES - Rosana, Martha; Wafa, Syahidatul; Tahapary, Dicky Levenus; Tarigan, Tri Juli Edi; Soewondo, Pradana; Yunir, Em (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Recent study at our tertiary referral hospital showed that the rate of severe hypoglycemia among type 2 diabetes mellitus (T2DM) outpatients was 34%. Our study aims to examine patients’ comprehension of hypoglycemia and its associated factors. METHODOLOGY This cross-sectional study used data from a study reporting rates of severe hypoglycemia conducted in our hospital. Patients’ comprehension of hypoglycemia was defined as patients’ ability to define cut-off value of hypoglycemia and mention at least 3 neuroglycopenic symptoms. RESULTS Out of 291 patients, 62.9% were women and the mean age was 59.9 (± 9.36) years. The median HbA1c was 7.5% (range: 5.1-14.3) and the median diabetes duration was 12 (range: 1-43) years. There were only 63 (21.7%) patients who had comprehension of signs and symptoms of hypoglycemia. Factors associated were poor comprehension of hypo- glycemia were the following: 1. Age >60 years (OR 0.45; p=0.006; 95% CI 0.25, 0.80), 2. HbA1c ≤ 7.5% (OR 0.53; p=0.026; 95% CI 0.30, 0.93), 3. Education level ≤9 years (OR 0.39; p=0.013; 95% CI 0.18,0.84) and (4) Use of sulfonylurea only (OR 0.49; p=0.025; 95% CI 0.27,0.92). CONCLUSION The proportion of patients with comprehension of hypoglycemia was low. Older age, lower education level, poorer glycemic control, and use of sulfonylurea are associated factors of patients’ comprehension of hypoglycemia. Our findings suggest the lack of effective diabetes education and further studies are needed to evaluate the need for a better diabetes education structure for our T2DM patients.